Observation and numerical simulation of terrain-induced airflow leading to low level windshear at the Hong Kong International Airport based on Range-Height-Indicator scans of a LIDAR - Pak Wai Chan; P. Cheung; K. K. Lai (Meteorologische Zeitschrift, 2024)
A Doppler Light Detection And Ranging (LIDAR) system is set up downstream of a small hill of Lantau Island near the Hong Kong International Airport to perform range-height-indicator (RHI) scans to monitor airflow disturbances by the terrain in a tropical cyclone case and to study the feasibility of alerting the low level windshear to be encountered by the aircraft leaving the airport. This is the first time that RHI scans are performed regularly downstream of the small hill. The scans show many interesting features of terrain-disrupted airflow, including tiny vortex of reverse flow and higher-speed wind streaks. The latter are found to be associated with the low level windshear reported by the pilots. The airflow features are simulated using a high resolution numerical weather prediction model. It turns out that the higher-speed wind streaks could be reproduced successfully. However, the reverse flow does not show up well in the simulation.